2014
DOI: 10.4172/2168-9547.s1-001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Characterization of Culturable Antibiotic Producing Streptomyces from Rhizospheric Soils

Abstract: Streptomyces spp. were isolated from rhizospheric soils collected from Ngaka Modiri Molema District, North West Province, South Africa. Ten of these bacterial isolates were found to exhibit broad spectrum antimicrobial activity against test organisms with varying degree of activity. The cultural characteristics of the bacterial isolates were consistent with that of the members of the genus Streptomyces. Molecular identification of the potent bacterial isolates was carried out by amplifying the 16S rDNA gene; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…(Kates 2012), this can also make it very resistant to biomolecules. The bacteria used for the tests were resistant to at least one known antimicrobial agent (Adegboye and Babalola 2013). Antagonistic assay against selected bacterial pathogens was carried out on the crude extracts of VOCs reveals that butanol extracts showed more antagonism against the selected pathogens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(Kates 2012), this can also make it very resistant to biomolecules. The bacteria used for the tests were resistant to at least one known antimicrobial agent (Adegboye and Babalola 2013). Antagonistic assay against selected bacterial pathogens was carried out on the crude extracts of VOCs reveals that butanol extracts showed more antagonism against the selected pathogens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of AHLs producing, as well as biofilm forming, bacterial isolates in this study was carried out by advanced molecular biology technique based on 16S rRNA gene sequence analysis. Analysis of nucleotide sequences has proved to be a powerful technique for phylogenetic characterization of bacteria [17]. The nucleotide blast analysis of complete 16S rRNA gene sequences form 32 bacterial isolates with the sequences available in the NCBI database demonstrated that they belong to eight different genera.…”
Section: Resultsmentioning
confidence: 99%
“…They can also provide an advantage to hosts when they target important host pathogens. For example, Actinobacteria such as Streptomyces are known for their production of antimicrobial secondary metabolites and are commonly found in the insect gut microbiome (Chevrette et al, 2019) and in the rhizosphere (Boukaew and Prasertsan, 2014;Adegboye and Babalola, 2013;Chen et al, 2018). In the genome of the plant-beneficial S. globisporus SP6C4 27 biosynthetic gene clusters encoding secondary metabolites were predicted (L. Pronk, unpublished results).…”
Section: Antimicrobial Compoundsmentioning
confidence: 99%